Seismic Risk of Buried Pipelines - C. Bacha; M. Zoutat; M. Mekki, (Algerian Journal of Research and Technology (AJRT), 2022)
A pipeline is a tubular section or hollow cylinder, usually of circular cross-section, used mainly to convey substances which can flow (fluids). It plays a crucial and essential role in human life and in economic development. The resilience ofthose systems under extreme events as earthquakes is a primary requirement, especially when largeamount of toxic and flammable material is transported.So, the present work will treat the seismic risk on the buried pipelines with respect to the seismic hazard and the vulnerability.